Avoiding routine postoperative voiding cystourethrogram: Predicting radiologic success for endoscopically treated vesicoureteral reflux - Wang, Peter (Zhan Tao); Abdelhalim, Ahmed; Walia, Arman; Wehbi, Elias; Dave, Sumit; Khoury, Antoine (Canadian Urological Association Journal, 2018)
Introduction: Variability in the success rates for the endoscopic correction of vesicoureteral reflux (VUR) has prompted a debate regarding the use of routine postoperative voiding cystourethrogram (VCUG). This study examines the predictive performance of intraoperative mound morphology (IMM) and the presence of a postoperative ultrasound mound (PUM) on radiologic success, as well as investigates the role of using these two predictive factors as a composite tool to predict VUR resolution after endoscopic treatment. Methods: This retrospective study included children with primary VUR who underwent endoscopic correction with a double hydrodistension-implantation technique (HIT) and dextranomer/ hyaluronic acid copolymer. IMM was assessed intraoperatively. The presence of a PUM and VUR resolution were assessed by postoperative ultrasound (US) and VCUG, respectively. Radiologic success was defined as VUR resolution. Results: A total of 70 children (97 ureters) were included in the study. The overall radiologic success rate was 83.5%. There was no statistically significant association between radiologic success and IMM (85.2% with excellent and 87.5% with “other” morphology; p=0.81). The sensitivity and specificity of PUM for radiologic success in this study was 98% and 71%, respectively, while the sensitivity and specificity of the combined prediction model were 81.9% and 85.7%, respectively. Conclusions: We objectively demonstrated that IMM was a poor predictor of radiologic success and should be used with caution. In addition, the performance of a combined prediction model was inferior to the presence of a PUM alone. As such, selective use of postoperative VCUG may be guided solely by the presence of a PUM.